Pengaruh Inokulasi Bakteri Terhadap Pertumbuhan Awal Jarak Pagar (Jatropha curcas L.) - Widawati, Sri; Rahmansyah, Maman (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTBacterial inoculants affect the early growth of Jatropha (Jatropha curcas L). Genera ofAzotobacter, Bacillus, Chromobacterium, Citrobacter, Nitrosomonas, Rhizobium, andSpaerotillus natans were soil bacterial isolates. The soil was collected from numerous placesaround Pontianak, West Kalimantan. Those isolates were used as inoculants, and formulatedto single and mixed bacterial inoculants, then used to stimulate the early growth of jatrophaseedling in 15 weeks at greenhouse condition. Bacterial inoculations caused better growthperformance compared to its control as pure soil garden medium without inoculations, andneither to bare soil dresses with compost. In the presence of inoculants, plant height wasaccelerated quickly while other inoculants affected to stalk diameter development. Daily growthperformance of jatropha peaked in 8 and 11 weeks after inoculation of Citrobacter andNitrosomonas bacterial component were used as single inoculant, respectively. The increasingof shoot biomass accumulation was three times as caused by single inoculants (Bacillus sp),and the highest one up to four times of biomass weight caused by a mixture inoculants asconsortium of Azotobacter, Bacillus, and Nitrosomonas spp. That selective inoculant hasopportunity to be used for jatropha farming, and this basic study is meaningful to jatropacultivation for standing to bio-fuel resources.Keywords: Jatropha curcas L., inoculants, Azotobacter, Bacillus, Chromobacterium,Citrobacter, Nitrosomonas, Rhizobium , Spaerotillus natans.Kata kunci: Jatropha curcas L., inoculants, Azotobacter, Bacillus, Chromobacterium,Citrobacter, Nitrosomonas, Rhizobium , Spaerotillus natans.